CLIL teacher assessment literacy: A scoping review - Liu, Jiajia Eve; Lo, Yuen Yi; Xin, Jieting Jerry (Teaching and teacher education, 2023)
In Content and Language Integrated Learning (CLIL) programmes, students learn content subjects through their additional language. The global spread of CLIL has raised concerns about teachers' professional development needs, and their assessment literacy is an essential one. This scoping review synthesises 60 theoretical and empirical articles on CLIL teachers' assessment literacy. The findings illustrate some prominent themes related to CLIL teachers' assessment literacy, identify areas that have been under-researched, and validate and refine a theoretical framework of CLIL teachers’ assessment literacy. This framework presents important dimensions of conceptions, knowledge and practices of CLIL assessment, with mediation of contextual factors.